2017
DOI: 10.7883/yoken.jjid.2015.616
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the M Protein Gene in Group C and Group G Streptococci Isolated from Patients in Thailand

Abstract: SUMMARY:We surveyed group C and group G b-hemolytic streptococci for emm and emmL (emm -like) genes which encode the M protein, as well as determined their antimicrobial susceptibilities. A total of 97 isolates 79 GCS/GGS isolates and 18 isolates from other groups were tested for the M protein gene by PCR. Focusing on invasive infections with group A (GAS), group C (GCS), and group G (GGS) b-hemolytic streptococci isolated from blood, the M protein gene was found in 90.0z, 84.6z, and 78.3z of isolates, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, this hypothesis may be applicable only for SDSE isolates from human sources, given that the isolates from animal sources are often emm non-typable [ 2 ]. Although our study could not find any associations due to typing of only 1 isolate, the amplified type ( stL2764 ) in this study has already been documented in several surveys of the pig, human, and horse SDSE [ 2 24 32 33 ]. Among them, Pinho et al [ 2 ] strongly doubted that the horse isolate identified as stL2764 had zoonotic potential.…”
Section: Discussionmentioning
confidence: 43%
“…However, this hypothesis may be applicable only for SDSE isolates from human sources, given that the isolates from animal sources are often emm non-typable [ 2 ]. Although our study could not find any associations due to typing of only 1 isolate, the amplified type ( stL2764 ) in this study has already been documented in several surveys of the pig, human, and horse SDSE [ 2 24 32 33 ]. Among them, Pinho et al [ 2 ] strongly doubted that the horse isolate identified as stL2764 had zoonotic potential.…”
Section: Discussionmentioning
confidence: 43%